Kepolisian negara RI (UU RI No.2 Th.2002) & Pertahanan Negara (UU RI No.3 Th.2002) - [Tidak Terdaftar] (Eko Jaya, 2002)
Kepolisia Negara RI (UU RI No.2 Th.2002) & Pertahanan Negara (UU RI No.3 Th.2002)